Cost-effectiveness analysis of treatments for the first episode of catastrophic antiphospholipid syndrome: A study based on the catastrophic antiphospholipid syndrome registry. (February 2022) - Quintana-López, Gerardo; Rodríguez-Pintó, Ignasi; Maldonado-Cañón, Kevin; Gerard Espinosa,; Diaz-Rojas, Jorge; Cervera, Ricard
Background: Treatments for catastrophic antiphospholipid syndrome (CAPS) rose from recommendations and consensus of international experts based on case series or case reports. We aimed to evaluate the treatment scheme with the best cost-effectiveness ratio associated with lower mortality as a high-impact clinical benefit. Methods: The CAPS Registry was used as our source of structured data on the different therapeutic strategies, their frequency, and their effectiveness (survival). Starting from around 50 different schemes, we identified those with a mortality of less than 33% within the 18 most frequently utilized. After applying the efficiency frontier method, we included two schemes to conduct a cost-effectiveness analysis from the Colombian healthcare sector perspective. Scheme 1 (Glucocorticoids + Anticoagulation + Anti-aggregation + Intravenous IgG immunoglobulin) and scheme 2 (Glucocorticoids + Anticoagulation + Anti-aggregation + Plasma exchange) were compared in terms of costs and survival. Deterministic and probabilistic sensitivity analyses (Monte Carlo simulation) were conducted to evaluate model robustness and uncertainty. Results: Our analysis uses the information corresponding to 427 cases from the CAPS registry, the majority being women (68.8%), with a mean age of 45.7 years and bearing general mortality of 38.17% (female: 38.4%, male: 37.5%). Scheme 2 was the cost-effective strategy over scheme 1. The results were robust on discrete sensitivity analysis and probability sensitivity analysis (Monte Carlo simulation). Conclusion: To our knowledge, this is the first economic evaluation focused on the treatment of CAPS. For the Colombian health system, schemes 1 and 2 have similar behavior; nevertheless, scheme 2 represents the best cost-effectiveness ratio. This treatment approach is highly susceptible to the allocation of resources by the system and beneficial in terms of health outcomes.